A multicenter registry of neuropsychiatric outpatients in Korean medicine hospitals (KMental): Protocol of a prospective, multicenter, registry study. Issue 49 (9th December 2022) - Suh, Hyo-Weon; Ko, Youme; Moon, Seunghwan; Kim, Jong Woo; Chung, Sun-Yong; Hong, Sunggyu; Lee, Hyun Woo; Huang, Ching-Wen; Jang, Bo-Hyoung
Abstract : Introduction: Mental health is an important global health concern. In Korea, many people visit Korean medicine clinics due to Stagnation syndrome and Hwabyung (cultural idioms of distress). Methods and analysis: We established a research collaboration comprising of professionals from 8 Korean medicine hospitals and planned a prospective, multicenter registry study. Demographic, socioeconomic, and clinical data will be collected from patients with mental disorders visiting the Korean medicine neuropsychiatric department of Korean medicine hospitals. We will include major psychiatric diagnoses related to neurosis and Korean traditional mental disorders such as Stagnation syndrome and Hwabyung. We expect to identify comprehensive characteristics of participants, measure the severity of their symptoms or distress, and investigate patterns of Korean medicine interventions and treatment responses for both the short-term and long-term (at least 4 years). Additionally, this study will include Health Insurance Review & Assessment Service data to analyze the medical use of registered patients before and after registration, in case the participant submits the consent form for personal information collection and use. To analyze the effectiveness of Korean medicine treatment for the participants, stratified or corrected analyses of age, sex, and diagnosis will be performed. The difference in the change in the psychometric measurements, quality of life measured by short form 36, and quality-adjusted life years will be calculated to evaluate the effectiveness of Korean medicine treatment.